Q: What is the inverse of y equals 4x - 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

y=x+2/4 (x+2 is all over four)

y=xsquared-4x+2

4x-y+7=0

You have 2 equations and 2 unknowns so you can solve 2x-3y = -11 y = 4x -3 2x - 3y = -11 -4x + y = -3 multiply 1st equation by 2 both sides: 4x-6y = -22 -4x + y = -3 add: -5y = -25 y = 5 substitute y = 5 into either equation: -4x+y = -3 -4x +5 = -3 -4x = -8 x = 2

y = 2x-5 4x-y = 7 => y = 4x-7 2x-5 = 4x-7 2x-4x = 5-7 -2x = -2 x = 1 Therefore by substituting: x = 1 and y = -3

Related questions

To find the inverse, replace y with x, and x with y. So, the inverse of the equation is: x = 4yWhich is equal to:y = x/4

2

6

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

The inverse of an equation is rewriting it as a function of the other variable. Simply solve the equation for x instead of y. y=9x can be written as x= (1/9)y --> fy=y/9◄ y=4x+6 (or 4x+6=y) -> 4x=y-6 -> x=(y-6)/4 --> gy=(y-6)/4■

6

y=x+2/4 (x+2 is all over four)

y equals 2

y=xsquared-4x+2

2x-y=5, y=2x-5 4x+y=4, y=4-4x 2x-5=4-4x 6x=9 x=3/2 y= 2(3/2)-5 y=-2

2

If: y = x -2 and 7y -4x = 10 Then: x = 8 and y = 6